Biallelic mutations in CYP26B1: A differential diagnosis for Pfeiffer and Antley–Bixler syndromes. Issue 10 (13th July 2016) - Morton, Jenny E. V.; Frentz, Sophia; Morgan, Tim; Sutherland‐Smith, Andrew J.; Robertson, Stephen P.
Abstract : Recently, a newly identified autosomal recessive skeletal dysplasia was described characterized by calvarial abnormalities (including cranium bifidum, coronal, and lambdoid synostosis), oligodactyly, femoral bowing, narrow thorax, small pelvic bones, and radiohumeral synostosis. In the two families described, a more severe phenotype led to in utero lethality in three siblings while in a single patient in a second family the phenotype was sufficiently mild to allow survival to 5 months of age. The disorder is caused by biallelic missense mutations in CYP26B1, which encodes for a cytochrome P450 enzyme responsible for the catabolism of retinoic acid in a temporally and spatially restricted fashion during embryonic development. Here, we provide the third family affected by the disorder and the first affected individual to survive beyond infancy. This woman homozygous for c.1303G>A; p.(Gly435Ser) in CYP26B1, which was associated with multisutural synostosis, radiohumeral synostosis, normal bone mineral density, and apparent intellectual disability, a phenotype with significant similarities to Antley–Bixler and Pfeiffer syndromes. © 2016 Wiley Periodicals, Inc.